Essai sur le rôle d’une espèce végétale rustique pour un développement durable de la steppe algérienne - Mohammedi Halima; Labani Abderrahmane; Benabdeli Khéloufi (Développement Durable et Territoires)
The steppe in Algeria is a strategic space as regards to the control of desertification, it covers more than 20 million hectares and knows an important degradation. Various programmes of protection and rehabilitation concerning this space failed and are at the origin of the aggravation of this degradation. A synthesis of the causes of this failure will make it possible to propose a new approach centered on the introduction of a very rustic plant species and whose ecological impact could save the steppe.